KEMAMPUAN MEMPRESENTASIKAN TEKS BIOGRAFI DI KELAS X SMA SWASTA KATOLIK BUDI MURNI 2 MEDAN - Damyyanus Tarigan (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2024)
This study aims (1) to determine the ability to present biography text in class X SMA Swasta Katolik Budi Murni 2 Medan with expository learning model; (2) to determine the ability to present biography text in class X SMA Swasta Katolik Budi Murni 2 Medan with talking stick learning model assisted by audio visual media; (3) to determine the effect of talking stick learning model assisted by audio visual media on the ability to present biography text in class X SMA Swasta Katolik Budi Murni 2 Medan. The population in this study were all grade X students of SMA Swasta Katolik Budi Murni 2 Medan which amounted to 246 students. The samples in this study were students of class X-2 as the experimental class and X-3 as the control class, each totaling 34 students. This study used a quasi-experimental method. In this study, the research design used was two group post-test only control design using a quantitative approach. The research instrument used was a performance test in the form of a post-test presenting a national hero. The results showed (1) The ability to present biography text in class X SMA Swasta Katolik Budi Murni 2 Medan with the expository learning model was classified in the sufficient category with an average score of 69.21; (2) The ability to present biography text in class X SMA Swasta Katolik Budi Murni 2 Medan with the talking stick learning model assisted by audio-visual media was classified in the good category with an average score of 82.59; (3) There was a significant difference in average scores between the experimental class and the control class which indicated that the talking stick learning model was more effective in improving the ability to present biography text in class X SMA Swasta Katolik Budi Murni 2 Medan. Through hypothesis testing, T_hitung = 8.26 and T_table = 1.99 were obtained. Thus it can be concluded that T_hitung > T_table is 8.26> 1.99 so that H_0 is rejected and H_1 is accepted, meaning that there is an effect of using the talking stick learning model assisted by audio-visual media on the ability to present biographical text in class X SMA Swasta Katolik Budi Murni 2 Medan.